Bioconversion of Crude Glycerol into 1,3-Propanediol(1,3-PDO) with Bioelectrochemical System and Zero-Valent Iron Using Klebsiella pneumoniae L17 - Da Seul Kong; Eun Joo Park; Sakuntala Mutyala; Minsoo Kim; Yunchul Cho; Sang Eun Oh; Changman Kim; Jung Rae Kim (Energies, 2021)
Crude glycerol is a major byproduct in the production of biodiesel and contains a large number of impurities. The transformation of crude glycerol into valuable compounds such as 1,3-propanediol (1,3-PDO) using clean and renewable processes, like bioconversion, is an important task for the future of the chemical industry. In this study, 1,3-PDO bioproductions from crude and pure glycerol were estimated as 15.4 ± 0.8 and 11.4 ± 0.1 mmol/L, respectively. Because 1,3-PDO is a reductive metabolite that requires additional reducing energy, external supplements of electron for further improvement of 1,3-PDO biosynthesis were attempted using a bioelectrochemical system (BES) or zero-valent iron (ZVI). The conversions of crude and pure glycerol under electrode and iron-based cultivation were investigated for 1,3-PDO production accompanied by metabolic shift and cell growth. The BES-based conversion produced 32.6 ± 0.6 mmol/L of 1,3-PDO with ZVI implementation.